Dietary Intake and Asthma in Preschoolers: A Logistic Lasso Regression Analysis - Qu, Yangming; Pan, Chengliang; Guo, Shijie; Wu, Hui (Frontiers in Pediatrics, 2022)
Background Asthma is a common chronic disease among children, especially preschoolers. Some evidence suggested that diet may play a role in asthma, but the results of current studies are conflicting. The objective of our study was to identify the association between dietary intake and asthma in preschool children aged 2-5 years. Methods We selected preschoolers aged 2-5 years with asthma diagnosis, diet, and BMI data from the NHANES database and deleted missing values. In a selected population, children with self-reported asthma were included in the final sample. Among children without self-report asthma, we further used propensity score matching (PSM) to match age and sex for sampling, maintaining a ratio of 1:4 for cases. All statistical analyses were performed using R Statistical Software. The "survey" package was used in the univariate analyses. The “glmnet” package was used to fit the logistic LASSO regression. Results There were 269 children with self-reported asthma and 1076 children without self-reported asthma included in our study. Univariate analysis showed that there were significant differences in ethnicity and dietary zinc intake between asthmatic children and asthmatic children. After adjusting for all dietary and demographic variables, the results of Logistic Lasso regression analysis showed that non-Hispanic black (β = 0.65), vitamin B12 (β = 0.14) and sodium (β = 0.05) were positively associated with childhood asthma, while Vitamin K (β = -0.04) were negatively associated with childhood asthma. Conclusion In conclusion, our study confirms that non-Hispanic black and dietary sodium intake are associated with a higher risk of asthma in preschoolers. In addition, our study found that dietary vitamin B12 was positively associated with childhood asthma, while vitamin K was negatively associated with childhood asthma. However, the use of Lasso in the assessment of dietary intake and asthma needs to be confirmed in other prospective studies and further research is required.